COMPUTATIONAL FLUID DYNAMICS SIMULATION OF ABRASIVE FLOW MACHINING OF BIOMATERIALS - Sai Venkata Phanindra Chary (Yeshwantrao Chavan College of Engineering, India, 2021)
The AFM process uses a self-deforming tool. In the areas where the flow is restricted the abrasion takes place removing the material and generating finer surfaces. As time passed, different kinds of AFM have been developed to maximize productivity and enhance the surface finish. Factors that influence the material removal and surface finish in the AFM process are particle size, extrusion pressure, piston velocity, and media viscosity. Carrying out experiments for all the process parameters and obtaining better process parameters of AFM, precisely, in less time is tough to achieve. Computational Fluid Dynamics (CFD) simulation was employed to determine machining parameters. In this project, the parameters obtained theoretically and from the CFD simulation are compared with the available experimental data and then the better machining parameters for the surgical implant materials ASTM F1537 wrought Co-28Cr-6Mo alloy and Ti6Al4V alloy were also determined by using CFD simulation.